Production and covalent immobilisation of the recombinant bacterial carbonic anhydrase (SspCA) onto magnetic nanoparticles - Rosa Perfetto; Sonia Del Prete; Daniela Vullo; Giovanni Sansone; Carmela M.A. Barone; Mosè Rossi; Claudiu T. Supuran; Clemente Capasso (Taylor & Francis Group, 2017)
Carbonic anhydrases (CAs; EC 4.2.1.1) are metalloenzymes with a pivotal potential role in the biomimetic CO2 capture process (CCP) because these biocatalysts catalyse the simple but physiologically crucial reaction of carbon dioxide hydration to bicarbonate and protons in all life kingdoms. The CAs are among the fastest known enzymes, with kcat values of up to 106 s−1 for some members of the superfamily, providing thus advantages when compared with other CCP methods, as they are specific for CO2. Thermostable CAs might be used in CCP technology because of their ability to perform catalysis in operatively hard conditions, typical of the industrial processes. Moreover, the improvement of the enzyme stability and its reuse are important for lowering the costs. These aspects can be overcome by immobilising the enzyme on a specific support. We report in this article that the recombinant thermostable SspCA (α-CA) from the thermophilic bacterium Sulfurihydrogenibium yellowstonense can been heterologously produced by a high-density fermentation of Escherichia coli cultures, and covalently immobilised onto the surface of magnetic Fe3O4 nanoparticles (MNP) via carbodiimide activation reactions. Our results demonstrate that using a benchtop bioprocess station and strategies for optimising the bacterial growth, it is possible to produce at low cost a large amount SspCA. Furthermore, the enzyme stability and storage greatly increased through the immobilisation, as SspCA bound to MNP could be recovered from the reaction mixture by simply using a magnet or an electromagnetic field, due to the strong ferromagnetic properties of Fe3O4.